Future research trends in understanding the mechanisms underlying allergic diseases for improved patient care - Breiteneder, Heimo; Diamant, Zuzana; Eiwegger, Thomas; Fokkens, Wytske J; Traidl-Hoffmann, Claudia; Nadeau, Kari; O'Hehir, Robyn E; O'Mahony, Liam; Pfaar, Oliver; Torres, Maria J; Wang, De Yun; Zhang, Luo; et al. (Allergy, 2019)
The specialties of allergy and clinical immunology have entered the era of precision medicine with the stratification of diseases into distinct disease subsets, specific diagnoses, and targeted treatment options, including biologicals and small molecules. This article reviews recent developments in research and patient care and future trends in the discipline. The section on basic mechanisms of allergic diseases summarizes the current status and defines research needs in structural biology, type 2 inflammation, immune tolerance, neuroimmune mechanisms, role of the microbiome and diet, environmental factors, and respiratory viral infections. In the section on diagnostic challenges, clinical trials, precision medicine and immune monitoring of allergic diseases, asthma, allergic and nonallergic rhinitis, and new approaches to the diagnosis and treatment of drug hypersensitivity reactions are discussed in further detail. In the third section, unmet needs and future research areas for the treatment of allergic diseases are highlighted with topics on food allergy, biologics, small molecules, and novel therapeutic concepts in allergen-specific immunotherapy for airway disease. Unknowns and future research needs are discussed at the end of each subsection.
Keywords: Hypersensitivity; imunologická tolerance; výzkum; Quality Improvement; alergie; Humans; Immune Tolerance; Patient Care; Health Services Needs and Demand; interakce hostitele a patogenu; životní prostředí; alergeny; zánět; Environment; péče o pacienta; zlepšení kvality; neuroimunomodulace; Precision Medicine; Disease Susceptibility; Immunomodulation; Allergens; Inflammation; zdravotnické služby - potřeby a požadavky; náchylnost k nemoci; vystavení vlivu životního prostředí; lidé; Neuroimmunomodulation; imunomodulace; Host-Pathogen Interactions; individualizovaná medicína; Environmental Exposure; Research